An Enzyme Cascade Reaction for the Recovery of Hydroxytyrosol Dervatives from Olive Mill Wastewater. Issue 11 (8th July 2022) - Terholsen, Henrik; Kaur, Jasmin; Kaloudis, Nikolaos; Staudt, Amanda; Pavlidis, Ioannis V.; Bornscheuer, Uwe T.
Abstract: The valorization of olive mill wastewaters (OMWW), a by‐product of the olive milling, is getting rising attention. Lipophilization of the main phenolic compound 3‐hydroxytyrosol (HT) could facilitate its extraction. An immobilized variant of the promiscuous hydrolase/acyltransferase from Pyrobaculum calidifontis VA1 (PestE) was used to perform acetylation in water using ethyl acetate as acyl donor. PestE was used in a segmented flow setting to allow continuous operation. Additionally, HT precursors were made accessible by pretreatment with almond β ‐glucosidase and the hydrolytic activity of PestE_I208A_L209F_N288A. Abstract : Olive mill wastewater (OMWW) is a major by‐product of olive oil extraction and requires special treatment due to the polyphenolic compounds it contains. We developed an enzymatic cascade reaction for the deglycosylation and acetylation of oleuropein and 3‐hydroxytyrosol to facilitate their extraction.